ETHICAL LEADERSHIP AND EMPLOYEE PERFORMANCE IN PRIVATE HIGHER EDUCATION UNIVERSITIES AND INSTITUTES OF KARACHI - Hira Zafar; Muhammad Faisal Sultan; Muhammad Adeel Mannan (International Journal of Contemporary Issues in Social Sciences, 2024)
This study is conducted to understand the impact of ethical leadership on employee performance in higher education institutes in Karachi. Therefore, after a thorough survey of the literature a simple and unique model has been developed to reflect the indirect association of ethical leadership with employee performance. The model is blended with intrinsic motivation which is the prime factor that ethical leaders have used to foster employee performance. The sampling frame for this study includes all the private institutes of Karachi and the sample used for the study is based on 250 experienced and permanent faculty members from faculties of management sciences. Analysis has been made through SMART-PLS and analytics indicated that ethical leadership affects the intrinsic motivation of employees & employee performance in the private higher educational institutes of Karachi.